GluA2-lacking AMPA receptors in hippocampal CA1 cell synapses: evidence from gene-targeted mice - Rozov, Andrei; Sprengel, Rolf; Seeburg, Peter H. (Frontiers in Molecular Neuroscience, 2012)
The GluA2 subunit in heteromeric AMPA receptor channels restricts Ca2+ permeability and block by polyamines, rendering linear the current-voltage relationship of these glutamate-gated cation channels. Although GluA2-lacking synaptic AMPA receptors occur in GABA-ergic inhibitory neurons, hippocampal CA1 pyramidal cell synapses are widely held to feature only GluA2 containing AMPA receptors. A controversy has arisen from reports of GluA2-lacking AMPA receptors at hippocampal CA3-to-CA1 cell synapses and a study contesting these findings. Here we sought independent evidence for the presence of GluA2-lacking AMPA receptors in CA1 pyramidal cell synapses by probing the sensitivity of their gated cation channels in wild-type mice and gene-targeted mouse mutants to philanthotoxin, a specific blocker of GluA2-lacking AMPA receptors. The mutants either lacked GluA2 for maximal philanthotoxin sensitivity, or, for minimal sensitivity, expressed GluA1 solely in a Q/R site-edited version or not at all. Our comparative electrophysiological analyses provide incontrovertible evidence for the presence in wild-type CA1 pyramidal cell synapses of GluA2-less AMPA receptor channels.